Prediction Method of Maximum Propagation Angle in Parabolic Equation Model over Irregular Terrain - Rui Zhang; Hongguang Wang; Zhensen Wu; Leke Lin; Zhenwei Zhao (International Journal of Antennas and Propagation)
The parabolic equation (PE) model is effective for predicting signal propagation over irregular terrains. The shift map method of the PE model is highly accurate and widely used for terrain propagation predictions. The maximum propagation angle is a crucial parameter of the shift map model. Here, unreasonable values may result in incorrect results or further computations. However, the prediction formula used in existing literature is limited, thereby leading to inaccurate results. In this study, a maximum propagation angle prediction method was developed. The maximum propagation angle with terrain should be calculated as the sum of the maximum propagation angle without terrain and twice the maximum terrain slope angle. Hence, the selection criteria for the different models in the hybrid terrain model were reanalyzed. An accurate maximum propagation angle is key for the PE model over irregular terrains, as it ensures prediction accuracy and improves calculation speed.